Factors that contribute to becoming unbanked - Rhine, S.; Greene, William (2013)
The proportion of US families that are unbanked (i.ehave no type of checking or savings account) has steadily declined for more than two decades. Nonetheless, more than nine million families still do not participate in the financial mainstream, and roughly half these unbanked families previously held a traditional bank account. This study uses the 2004 longitudinal Survey of Income Program Participation to examine the dynamic process within which changes in families' circumstances contribute to their becoming unbanked. Our findings suggest that families are significantly more likely to become unbanked when there is a decline in family income, loss of employment, or loss of health insurance coverage. Race and ethnicity, level of education or family income, and marital or housing status are also important determinants of whether families participate in the financial mainstream or not. To our knowledge, this is the first analysis of the dynamic process by which families change bank status. © 2012 by The American Council on Consumer Interests.